Chinese foreign direct investment in Brazil : Evolution, trends and concerns over critical infrastructure - Barros Torres, Gabriel de (2020)
Fil: Barros Torres, Gabriel de. Pontificia Universidad Católica de Río de Janeiro; Brasil